Atoms Want to Be Free Too! Expanding the Critique of Intellectual Property to Physical Goods - Johan Söderberg; Adel Daoud (tripleC: Communication, Capitalism & Critique)
“Atoms are the new bits”. That is the latest buzz arising from the Californian trade press. What do we get when this dictum is sampled with the old rallying cry: “Information wants to be free”? We suggest that the predominant, bounded critique of intellectual property is thereby destabilised. Constitutive of that critique was the exceptionality attributed to information goods (bits) vis-a-vis tangible goods (atoms). It was thus intellectual property could be presented as something altogether different from private property. We recognise that this way of framing the issue has had tactical advantages, but contend that it has stood in the way of a deeper understanding of what intellectual property is. When the critique of proprietary software is expanded by an emerging movement for open hardware development, however, the boundary between intellectual property and property as such crumbles. This enables us to renew our critique of the political economy of information.